Comparação do comportamento alimentar das crianças com TEA nos ambientes familiar e escolar - Cardozo, Paloma Blanca Marchezini (Universidade Federal de São Carlos, 2024)
This research has as its concept to verify the influence of the family and school environment on the child with Autism Spectrum Disorder's (ASD) food behavior . It aimed to analyze and compare the food behavior of children with ASD in family and school environments. It is a qualitative exploratory research with discussion of data from the point of view of behavior analysis. Its data collection instrument is an interview, the eating behavior assessment scale in ASD (Lázaro et al., 2019) and the questionnaire proposed by Rocha et al (2019). The results are expected to contribute to the identification of the role of the family and school environment in the child's food development process and as the basis for the conduct of new investigations in psychology and special education.
Comparison of the food behavior of children with ASD in the family and school environments
Keywords: Transtorno do Espectro Autista; Autism Spectrul Disorder; Seletividade alimentar; Food selectivity; Família; Family; Escola; School; CIENCIAS HUMANAS::EDUCACAO